Paleozoic supracrustal rocks near Cheticamp, Nova Scotia - Currie, K. L. (Atlantic Geology, 1982)
Near Cheticamp, northwestern Cape Breton Island, a sequence of supracrustal rocks overlies and cuts granite previously dated at 530±44 million years, as veil as older, presumably Precambrian gneisses. Rhyolite dikes feeding the supracrustal sequence yielded zircons giving a U-Pb discordia age of 439±7 million years (late Ordovician or Silurian). The supracrustal rocks are overlain and cut by bimodal volcanies of the Fisset Brook Formation, previously dated by Rb-Sr isochron at 376±12 million years. Interpretation of the stratigraphic and geochronologlic data, together with petrochemical data on the volcanic rocks, shows that the rocks of the Cape Breton Highland underwent repeated cycles of deformation, uplift and granitic intrusion, rapidly followed by subsidence and emplacement of bimodal volcanic rocks. The repetitive and cyclic nature of the process suggests that throughout late Precambrian and early Paleozoic time these rocks remained in a single, cyclic, tectonic environment, rather than passing from one tectonic environment to another. RÉSUMÉ Près de Cheticamp, dans le nord-ouest de l'ile du Cap-Breton, une succession de roches supracrustales recouvre et coupe un granite daté antérieurement à 530±44 million d'années, ainsi que des gneiss plus vieux dont l'âge remonte vraisemblablement au Précambrien. Des dykes de rholite qui alimentent la succession supracrustale ont livre des zircons donnant un âge U-Pb "discordia" de 439±7 million d'années (Ordovicien tardif ou Silurlen). Les roches supracruatales sont recouvertes et coupées par des roches volcaniques bimodales de la formation Fisset Brook, datées anterieurement à 376±12 million d'années par isochrone Rb-Sr. L'interprètation des donnéea stratigraphiques et géochronologiques, alnsi que les données pétrochimiques des roches volcaniques, démontrent que les roches des ...